2018
DOI: 10.1155/2018/4528581
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Aqueous Extracts of Flos lonicerae Japonicae against Hydroquinone‐Induced Toxicity in Hepatic L02 Cells

Abstract: Hydroquinone (HQ) is widely used in food stuffs and is an occupational and environmental pollutant. Although the hepatotoxicity of HQ has been demonstrated both in vitro and in vivo, the prevention of HQ-induced hepatotoxicity has yet to be elucidated. In this study, we focused on the intervention effect of aqueous extracts of Flos lonicerae Japonicae (FLJ) on HQ-induced cytotoxicity. We demonstrated that HQ reduced cell viability in a concentration-dependent manner by administering 160 μmol/L HQ for 12 h as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…The increase of ROS can lead to lipid peroxidation, hence, oxidative stress is closely related to the pathogenesis of NAFLD (Mota et al, 2016). The enzymes SOD and GSH-px are important antioxidant enzymes that can prevent the damage of liver caused by reactive oxygen species (Gao et al, 2018) produced during oxidative stress. The MDA produced during lipid peroxidation can damage cell membranes and contribute to impaired cellular function (Perluigi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of ROS can lead to lipid peroxidation, hence, oxidative stress is closely related to the pathogenesis of NAFLD (Mota et al, 2016). The enzymes SOD and GSH-px are important antioxidant enzymes that can prevent the damage of liver caused by reactive oxygen species (Gao et al, 2018) produced during oxidative stress. The MDA produced during lipid peroxidation can damage cell membranes and contribute to impaired cellular function (Perluigi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In several regions of China, the former three are commonly used as foods. Several studies indicated that these four plants have anti-obesity or liver protection properties (6)(7)(8)(9)(10)12,13). Thus, we proposed that YZH may be a promising strategy for NAFLD management.…”
Section: Original Articlementioning
confidence: 93%
“…Compared with control, *P < 0.05, **P < 0.01, ***P < 0.001; compared with D-GalN, # P < 0.05, ## P < 0.01, ### P < 0.001. redox cycle of GSH and SOD [19,20]. SOD is an important antioxidant enzyme, that can catalyze the conversion of superoxide radical into H 2 O 2 , then continuously detoxify them to H 2 O [21][22][23]. Therefore, SOD protects hepatocytes from the harmful effects caused by superoxide radicals to a certain degree.…”
Section: Discussionmentioning
confidence: 99%